HENRY A. KISSINGER’S ARTICLE ON TERRORISM: A CRITICAL ANALYSIS - Mokhamad Toha Rudin (Rubikon : Journal of Transnational American Studies, 2014)
The aim of this study is to conduct a critical analysis of Kissinger’s article “America’s Assignment” on Newsweek 2004, and to elaborate US foreign policy toward Islam world and Terrorism after the end if the Cold War, this article also tries to find the ideology or tradition of American foreign policy reflected in Kissinger’s article “America’s Assignment”, and how is Realism ideology reflected in the article. The study employs library research in which the data gathered from books, journals, magazines, and internet. The study also employs Van Dijk’s critical linguistic model for the critical analysis of Kissinger’s “America’s Assignment”.The result of the study shows that Kissinger’s “America’s Assignment” reflects both "multilateralistrealist” and “realist-idealist” perspectives for the US foreign policy that the US government should employ. He argues that no single superpower in the world could manage the world order alone without the participants of other world countries. He opposes W. Bush’s unilateral foreign policy toward Iraq though he agrees to “the move toward empire (terrorist) must be halted immediately”. He also argues that bringing democracy into the world, especially Iraq and Muslim worlds, is necessary in order to set up the new world order. The study also shows that after the collapse of the Soviet Union, there is a new ideological and cultural conflict between Islam, especially the militant fundamentalist in the fringe of Islam, against the US (Western) globalization of democratization. The new conflict is also generated by the Western phobia toward Islam that can be traced back to the mid-century when the War of Crusade between Islam and Christianity happened.